"All boys and men can play football": A qualitative investigation of recreational football in prostate cancer patients. (August 2014) - Bruun, D. M.; Krustrup, P.; Hornstrup, T.; Uth, J.; Brasso, K.; Rørth, M.; Christensen, J. F.; Midtgaard, J.
Abstract : Evidence is accumulating that exercise‐based rehabilitation improves physical capacity and quality of life in cancer survivors. However, recruitment and persistence of male cancer patients in rehabilitation and physical activity are low and novel health promotion strategies are warranted. The purpose of this study was to gain an understanding of the meaning of recreational football as a team and interaction‐oriented health‐promoting activity in men with prostate cancer ( n  = 26). Qualitative data were collected through six focus group interviews ( n  = 4–6) and 20 h of participant observations. The two data sets were analyzed using framework analysis. The analysis produced 11 subthemes that were structured into three overarching themes: (a) motivational drivers; (b) united in sport; and (c) confirmation of own capacity. The findings indicated that participants regarded football as a welcome opportunity to regain control and acquire a sense of responsibility for own health without assuming the patient role, and football training legitimized and promoted mutual caring behavior in a male‐oriented context. In conclusion, the study suggests that football, due to its cultural representation of masculine ideals, may be a potent and unique strategy for increasing recruitment and adherence to physical activity in prostate cancer patients.